Clinicopathological Significance of Pluripotent Factors in Sinonasal Intestinal-Type Adenocarcinoma - Monaco, Federica; Vallieri, Alberto; Volpini, Luca; Foschini, Maria P; Filosa, Alessandra; Antolini, Enrica; Gioacchini, Federico Maria; Sollini, Giacomo; Pasquini, Ernesto; Iannella, Giannicola; Neuzil, Jiri; Amati, Monica; et al. (Cancers, 2025)
Background/Objectives: Sinonasal intestinal-type adenocarcinoma (ITAC) is a rare and aggressive tumor with a lack of specific symptoms, which leads to late diagnosis, and is characterized by frequent local recurrence and low survival rate. The stemness phenotype is one of the main causes leading to tumor proliferation, recurrence, and resistance to standard chemo/radiotherapy. Methods: In this study, genes encoding pluripotency-associated transcription factors, including KLF4, c-MYC, SOX2, OCT4 (Yamanaka factors), and NANOG were evaluated in malignant and non-malignant tissues of a cohort of 54 patients with ITAC, and their expression was related to patient outcome. The c-MYC, SOX2, and OCT4 levels were then confirmed in immunohistochemistry by adding ALDH1A1 as a factor involved in stemness. Results: KLF4, SOX2, and NANOG best distinguished cancer tissue from normal tissue with high sensibility and specificity. Low levels of KLF4, c-MYC, and NANOG and high expressions of SOX2 and OCT4 in tumor tissue correlated with poor overall survival (OS) and disease-free survival (DFS), respectively. Through multivariate analysis, type of surgery was found to be a significant prognostic factor along with c-MYC and OCT4. Notably, tumor positivity for c-MYC and ALDH1A1 was associated with longer disease-specific survival, thus suggesting their role as tumor suppressors. Conclusions: Our findings underline the stemness phenotype as a prognostic model for ITAC, supporting the clinical plausibility of Yamanaka factors in sinonasal cancer prediction.
Keywords: prognosis; SOX2; c-MYC; sinonasal cancer; OCT4; NANOG; ITAC; KLF4